2005
DOI: 10.1016/j.ejheart.2005.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of program and clinical outcomes of heart failure disease management incorporating specialist nurse-led heart failure clinics. A meta-regression analysis

Abstract: Objectives: To determine whether a hierarchy of effectiveness exists with respect to complexity of published protocols of heart failure (HF) disease management (DM) incorporating specialist nurse-led HF clinics. Data sources and study selection: We searched MEDLINE (1966( -November 2004, the Cochrane Library, article bibliographies, and contacted experts. Inclusion criteria were random allocation of at least 100 patients, specialist HF nurses, HF clinics, and readmission as an outcome measure. Data extraction:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 37 publications
(95 reference statements)
3
97
0
4
Order By: Relevance
“…The majority of these studies have been small singlecentre studies. During the past few years, a number of systematic reviews and larger randomized controlled trials (122)(123)(124)(125)(126)(127) have been performed to better estimate the effects of DMPs for HF patients on mortality and morbidity. These reviews generally found that DMPs reduce both all-cause and HF hospitalizations (122,123,(125)(126)(127).…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of these studies have been small singlecentre studies. During the past few years, a number of systematic reviews and larger randomized controlled trials (122)(123)(124)(125)(126)(127) have been performed to better estimate the effects of DMPs for HF patients on mortality and morbidity. These reviews generally found that DMPs reduce both all-cause and HF hospitalizations (122,123,(125)(126)(127).…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 99%
“…Multidisciplinary programs involving both a doctor and a nurse specializing in HF management appear to be a consistent requirement for these programs, with the potential for further benefit from the addition of other allied health professionals such as a pharmacist (122,123,126,127,138). Combinations of in-clinic and telephone follow-ups would appear to be important with entry into the DMP as soon as possible after discharge (122,124,125). The DMP should involve education, exercise and psychosocial counselling, selfcare supportive strategy, optimization of the medication regimen and medical referrals for deterioration (122,124,125,127).…”
Section: Acute Decompensated Hf During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Cullum et al (2005) other chronic diseases where patients require regular follow-ups and monitoring such as diabetes (Carey and Courtenay, 2007), coronary heart diseases (Page et al, 2005), heart failure (Phillips et al, 2005) and chronic obstructive pulmonary disease (Sridhar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Yet there were several systematic reviews of effectiveness in primary care (Horrocks et al, 2002, Laurant et al, 2004 and other chronic diseases (Carey and Courtenay, 2007, Page et al, 2005, Phillips et al, 2005, Sridhar et al, 2008, Taylor et al, 2005.…”
Section: Introductionmentioning
confidence: 99%